Helping to Learn Science - Saxena, A.B. (JOURNAL OF INDIAN EDUCATION, 2009)
The paper discusses in brief the characteristics of children’s ideas and how these could be dealt within the classroom, to make learning less stressful and more meaningful. Implications for teacher education are also discussed. This article also tries to explain how teachers should present themselves while dealing with the problems of students.